Determining The Key Factors That Influence Online Scores Given To Hotels On The Las Vegas Strip - Upadhyaya, Nikita; Kenekar, Apurva; Caicedo, Maria Alejandra; Berger, Paul D. (Archives of Business Research, 2018)
The objective of this paper is to determine the relationship between the final scores (ratings) that customers give to hotels on the Las Vegas Strip and two sets of factors/independent variables: traveler-related attributes and hotel attributes. The data used in the paper has been retrieved by data mining from the TripAdvisor website. Excel and SPSS are used to conduct statistical analyses including descriptive statistics, correlation, and simple and stepwise [multiple] regression. The findings provide information which may be of help to hotels in considering improvement to their services and additions/changes to their facilities.